2014
DOI: 10.21273/hortsci.49.3.294
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Germination Technique for Some Stone Fruit Species: the Embryo Isolated from Cotyledons Successfully Germinated without Cold Pre-treatment of Seeds

Abstract: Seeds of temperate fruit species need a long time to germinate as a result of their requirement of stratification or cold treatment. Therefore, fast and uniform germination techniques are desirable and important for fruit tree propagation and especially for breeding studies. The effects of combinations of benzylaminopurine (BAP) and gibberellic acid (GA3) on in vitro embryo germination of apricot, peach, and wild cherry were determined without seed cold pretreatment. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Principle commercial crops in this genus include peaches, nectarines, plums, prunes, apricots, cherries, and almonds. Seeds of stone fruits do not germinate immediately after harvest and a period of after ripening is essential for certain chemical and other changes to take place in the seed and for dormant embryo to grow [1]. Seed dormancy is a physiological phenomenon in plants, which is caused by external or internal factors, and prevents of seeds germination, even in optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Principle commercial crops in this genus include peaches, nectarines, plums, prunes, apricots, cherries, and almonds. Seeds of stone fruits do not germinate immediately after harvest and a period of after ripening is essential for certain chemical and other changes to take place in the seed and for dormant embryo to grow [1]. Seed dormancy is a physiological phenomenon in plants, which is caused by external or internal factors, and prevents of seeds germination, even in optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, García-Gusano et al [3] reported two independent dormancies in seeds of stone fruit a physical (external) and embryo (internal) dormancy which are essential for better survival and establishment of seedlings in the field. Seeds of temperate fruit species need a long time to germinate as a result of their requirement of stratification or cold treatment [1,4]. Seeds of temperate fruit species do not germinate as a result of seed dormancy even if conditions such as water, temperature, and oxygen are suitable for germination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of stone fruits do not germinate immediately after harvest and a period of after ripening is essential for certain chemical and other changes to take place in the seed and for dormant embryo to grow [21,22,23]. Seed dormancy is a physiological phenomenon in plants, which is caused by external or internal factors, and prevent of seeds germination, even in optimal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Seed dormancy may be caused due to hard seed coat, immature embryo, rudimentary embryo and inhibitors materials [23,24]. Seeds of temperate fruit species need a long time to germinate as a result of their requirement of stratification or cold treatment [21,23,25]. Seeds of temperate fruit species do not germinate as a result of seed dormancy even if conditions such as water, temperature, and oxygen are suitable for germination.…”
Section: Introductionmentioning
confidence: 99%